Effect of diabetes and HIV on radiographic manifestations of pulmonary tuberculosis - Berkowitz, Natacha (Centre for Infectious Disease Epidemiology and Research (CIDER), 2017)
Due to the epidemiological transition, diabetes prevalence in South Africa is increasing, while HIV prevalence remains high. Diabetes, along with HIV, has been found to be a significant risk factor for the development of tuberculosis. Early detection and treatment of tuberculosis is essential to prevent unwarranted morbidity and mortality. This hinges on efficient diagnostic methods and tools. The chest radiograph remains a cornerstone in pulmonary tuberculosis diagnosis, especially in those where microbiological evidence of disease is lacking. A study was conducted to investigate the chest radiographic presentation of pulmonary tuberculosis in patients with diabetes, as well as to analyse the effect of HIV comorbidity on this association. The study was conducted in Khayelitsha, Cape Town, an area with a high tuberculosis, HIV and diabetes burden. A literature review was conducted to identify the key features of pulmonary tuberculosis on chest radiograph for patients with diabetes and HIV. We found that patients with diabetes were more likely to have lower lung field infiltrates and increased cavitation, with glycaemic control affecting the presence of these findings. Patients with HIV presented more often with features of primary tuberculosis on chest radiograph, namely hilar and/or mediastinal adenopathy, diffuse reticulonodular infiltrate, and lower lung field (LLF) infiltrates and cavities. These features were influenced by degree of immunosuppression. This review also found that there was no literature describing the influence of HIV on the chest radiographic features of tuberculosis in patients with diabetes. This study was conducted between June 2013 - October 2015, where 377 patients with pulmonary tuberculosis, from Ubuntu and Site B primary care clinics in Khayelitsha, underwent posterior-anterior chest radiography. Chest radiographs were read using a CRRS tool. Participants with diabetes and tuberculosis (TBDM) had a higher proportion of lower lung field opacification (76,2%: 95% CI: 56,3 – 96,1) and were 3,92 times more likely to have LLF cavitations than patients with TB only. TBDM participants with HbA1c levels over 10% had more frequent LLF involvement overall (90,9% vs 61,9% p=0,052) and isolated LLF involvement (27,3% vs 3,6%; p= 0,019) than TB only participants. Both TBDM and TBDM participants with HIV (TBDMHIV) had higher proportions of isolated LLF lesions as compared to TB only participants (14,3% vs 3,6%; p=0,093 and 15,2% vs 3,6%; p = 0,039, respectively). As CD4 counts increased, there was an upward trend towards an increase in the proportion of cavitations for TBDMHIV participants, but this was not evident in participants with TB and HIV (TBHIV). This study confirms the atypical nature of chest radiograph in persons with TBDM, TBHIV and TBDMHIV, with diabetes driving the presence of lower lung field involvement. These findings can be used in bi-directional screening algorithms for patients with diabetes, with or without HIV and highlights the important role of radiographic examination in pulmonary tuberculosis.